Preparation of antihypertensive peptides from quinoa via fermentation with Lactobacillus paracasei. Issue 3 (19th July 2022) - Li, Shuai; Du, Gengan; Shi, Jiajun; Zhang, Lin; Yue, Tianli; Yuan, Yahong
Abstract: Quinoa is a pseudo‐cereal that is rich in protein and an ideal source of antihypertensive peptides. In this study, quinoa flour was fermented with Lactobacillus paracasei CICC 20241 via solid fermentation to produce antihypertensive peptides. The peptides were isolated and purified by ultrafiltration and gel chromatography, and then identified by liquid chromatography−tandem mass spectrometry. A total of 91 peptides were identified. In addition, five potential angiotensin‐converting enzyme (ACE) inhibitory peptides were synthesized with reference to in silico analysis. Among them, NIFRPFAPEL and AALEAPRILNL had the greatest inhibitory effect, with an IC50 of 49.02 and 79.72 µM, respectively. Inhibition dynamics and molecular docking indicated that NIFRPFAPEL formed eight hydrogen bonds with ACE residues Tyr523, Arg522, Glu384, Glu143, Glu123, Thr92, Tyr62, and Trp59. NIFRPFAPEL exerted a competitive inhibitory effect by interacting with residues Tyr523 and Glu384 of pocket S1. AALEAPRILNL exerted a noncompetitive inhibitory effect by forming eight hydrogen bonds with the inactive ACE site residues Ser516, Glu403, Ser355, Glu143, ARG124, and Asn70. These results confirmed that quinoa is a potential material for antihypertensive functional foods, while NIFRPFAPEL and AALEAPRILNL could be used for the development of antihypertensive functional foods or drugs. Abstract : Antihypertensive peptides were prepared by solid‐state fermentation of quinoa by Lactobacillus paracasei CICC 20241. Angiotensin‐converting enzyme​​​​​ (​​ACE) inhibitory peptides were isolated and identified as NIFRPFAPEL and AALEAPRILNL. NIFRPFAPEL was a competitive inhibitor of ACE and AALEAPRILNL was a noncompetitive one.